2(y-4)+5=3(y+2)
multiply the first bracket by 2
(2)(y)=2y
(2)(-4)=-8
multiply the second bracket by 3
(3)(y)=3y
(3)(2)=6
2y-8+5=3y+6
2y-3=3y+6
move 3y to the other side
sign changes from +3y to -3y
2y-3y-3=3y-3y+6
-y-3=6
move -3 to the other side
-y-3+3=6+3
-y=9
multiply both sides by -1 to get +y
(-1)(-y)=9(-1)
Answer:
y=-9
This is not a polynomial equation unless one of those is squared. As it stands x=-.833. If you can tell me which is squared I can help solve the polynomial.
Ok, that is usually notated as x^3 to be clear. I'll solve it now.
x^3-13x-12=0
Then use factor theorum to solve x^3-13x-12/x+1 =0
So you get one solution of x+1=0
x=-1
Then you have x^2-x-12 now you complete the square.
Take half of the x-term coefficient and square it. Add this value to both sides. In this example we have:
The x-term coefficient = −1
The half of the x-term coefficient = −1/2
After squaring we have (−1/2)2=1/4
When we add 1/4 to both sides we have:
x2−x+1/4=12+1/4
STEP 3: Simplify right side
x2−x+1/4=49/4
STEP 4: Write the perfect square on the left.
<span>(x−1/2)2=<span>49/4
</span></span>
STEP 5: Take the square root of both sides.
x−1/2=±√49/4
STEP 6: Solve for x.
<span>x=1/2±</span>√49/4
that is,
<span>x1=−3</span>
<span>x2=4</span>
<span>and the one from before </span>
<span>x=-1</span>
I hope this helps you
-4x-2y+4x+8y= -12-24
6y= -36
y= -6
-4x-2. (-6)= -12
-4x+12= -12
-4x= -24
x=6
(6, -6)
The correct answer is A. Think of this as a graph in the y=Mx+b form. When graphing these equations, you should be able to see that the lines for A and B match up with the picture. However, since everything below the line is shaded, this must mean that the graph includes everything under the line. Y must be less than everything that is input. The correct answer is A.
-R
Answer:
y=3/2x+7
Step-by-step explanation:
y=mx+b
m=3/2
b=7